Comparison of an increased waist circumference with a positive hydrogen breath test as a clinical predictor of lactose intolerance - Zapata Castilleja, Carlos Alberto; Castillega, M. D.; Montes Tapia, Fernando Félix; Treviño Garza, Consuelo; Martínez Cobos, María Cristina; García Cantú, Jesús; Vincenzo Arenas, Fabbri; O Escamilla, Norma de la; O Cavazos, Manuel Enrique de la (2017)
ABSTRACT Introduction. Lactose intolerance is a common disease in pediatrics, and its wrong diagnosis will lead to morbidity. The primary objective of this study was to assess the usefulness of an increased waist circumference during the hydrogen breath test as a predictor of lactose intolerance. The secondary objective was to analyze the impact of body mass index, waist circumference measurement, and age on the abdominal distension of patients with lactose intolerance. Population and methods. A total of 138 subjects aged 3 to 15 years were included. They underwent serial measurements of the waist circumference and hydrogen levels in the breath every 30 minutes over 3 hours during the hydrogen breath test. Results. Out of the entire sample, 35 (25.4%) patients had lactose intolerance. An increase of 0.85 cm in waist circumference compared to the baseline waist circumference results in a sensitivity of 88% and a specificity of 85% to predict lactose intolerance (odds ratio: 42.14, 95% confidence interval: 13.08-135.75, p ≤ 0.001). The body mass index and waist circumference measurement did not affect abdominal distension (p= not significant); however, age modified the time of distension. Conclusions. A 0.85 cm increase in waist circumference compared to the baseline waist circumference during the hydrogen breath test is a useful parameter for the diagnosis of lactose intolerance in pediatrics. Variations in relation to body mass index and waist circumference did not affect the usefulness of an increased waist circumference, unlike age. Key words: lactose intolerance, waist circumference, diagnosis, exhaled hydrogen breath, child.